Code essentials 4 : complying with the international code of marketing of breastmilk substitutes and subsequent WHA resolutions : a guide for regulators compliance staff - Joo Kean, Yeong; Bardsley, Megan Jessica; Ching, Constance; Allain, Jean-Pierre (IBFAN Sdn Bhd, 2018)
A guide specifically for regulators (or enforcement officers) and company compliance staff, Code Essentials 4 provides clear guidelines to help identify Code violations, and showcases some examples of how companies interpret Code provisions differently to serve their marketing needs. It has solid guidelines for companies to follow for their internal monitoring and Code compliance manuals, rendering systematic violations with no excuse. Nakladatelská anotace. Kráceno.
Keywords: Marketing; vytváření politiky; mezinárodní spolupráce; zákonodárství jako téma; Breast Feeding; Policy Making; Infant Formula; Legislation as Topic; politologie, politika, zdravotní politika; marketing; ekonomie, ekonomika, ekonomika zdravotnictví; International Cooperation; nutriční terapie, dietoterapie a výživa; náhražky mateřského mléka; kojení